The effects of resistance based post-activation performance enhancement on reaction time and change of direction in basketball players - Genç, S.; Günay, A. R.; Günay, E. (PLOS ONE, 2025)
The aim of this study was to investigate the effect of post-activation performance enhancement (PAPE) intervention with 80% one repetition maximum (1RM) resistance on change of direction (COD) and reaction time (RT) in basketball players. This study sixteen male basketball players (mean age: 20.25 years, height: 1.88 m, weight: 80.75 kg, training age: 10.12 years) were included. For this study, participants attended 3 experimental sessions in the laboratory. Firstly, anthropometric measurements of the participants were taken, then RT and COD were familiarized respectively, and then 1RMs were determined. Then, the participants randomly completed the first and second sessions. In the first session, a 20-minute standard warm-up (Wup) was performed. After the participants rested passively for 3 minutes after the Wup, RT and COD tests were measured at 1-minute intervals, respectively. The results obtained were considered as the control condition. In the second session, participants rested passively for 3 minutes after performing the PAPE (80% of 1RM - 5 rep) protocol. After the rest period, participants performed RT and COD with a 1-minute interval, respectively. The data were analyzed separately for RT (visual, auditory, and mixed) and COD test results in terms of Wup and Wup+PAPE. At least 48 hours of rest was allowed between the first and second sessions to ensure that fatigue from the previous test session did not affect the results. Wilcoxon test results showed that PAPE significantly reduced visual RT (p < .005), mixed RT (p < 0.013), and COD (p < 0.001), but not auditory RT (p < 0.068). The findings showed that PAPE is an effective method to improve COD and RT performance in sports such as basketball, where success is achieved through fast-paced play.